Encyclopedia of Global Archaeology 2014
DOI: 10.1007/978-1-4419-0465-2_1986
|View full text |Cite
|
Sign up to set email alerts
|

Maisières-Canal: An Open-Air Aurignacian Workshop

Abstract: Magnetists and thus should make use of those techniques. Although the field of Environmental Magnetism has continued its rapid development, archaeological applications over the past decade have tended to focus on field applications of susceptibility. There is thus much potential for expanded use of the entire range of magnetic techniques to answer questions relating to past climates, dating, formation, and postdepositional processes central to understanding the relationship of humans to their environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Crvenka-At's main interest is its lowland setting; an outlier in the Carpathian Basin's Aurignacian record. While lowland Aurignacian sites are occasionally encountered elsewhere in Europe (e.g., Masières Canal; Miller, 2014), it has previously been suggested that the occurrence of Aurignacian sites in short stratigraphic sequences in the Carpathian Basins foothills, between 43 and 30 ka BP are a genuine reflection of modern human behavioral preference for this specific biome (Hauck et al, 2018). Our results provide a first direct indication that modern humans made use of riparian landscapes possibly to avoid mountainous regions as a result of late Neanderthal territoriality until c. 39 ka cal BP in the Central Balkans (Alex, 2016, 112;Marín-Arroyo and Mihailović, 2017;Alex et al, 2019;Mihailović, 2020).…”
Section: Archeological and Paleoanthropological Implicationsmentioning
confidence: 99%
“…Crvenka-At's main interest is its lowland setting; an outlier in the Carpathian Basin's Aurignacian record. While lowland Aurignacian sites are occasionally encountered elsewhere in Europe (e.g., Masières Canal; Miller, 2014), it has previously been suggested that the occurrence of Aurignacian sites in short stratigraphic sequences in the Carpathian Basins foothills, between 43 and 30 ka BP are a genuine reflection of modern human behavioral preference for this specific biome (Hauck et al, 2018). Our results provide a first direct indication that modern humans made use of riparian landscapes possibly to avoid mountainous regions as a result of late Neanderthal territoriality until c. 39 ka cal BP in the Central Balkans (Alex, 2016, 112;Marín-Arroyo and Mihailović, 2017;Alex et al, 2019;Mihailović, 2020).…”
Section: Archeological and Paleoanthropological Implicationsmentioning
confidence: 99%